Management Style SMEs Development of Wooden Batik Centre - Aryan Torrido (Jurnal Manajemen dan Kewirausahaan, 2022)
Industrial centers are often used as places for small and medium enterprise (SMEs) development activities and sources of regional income. This includes wooden batik centers in the DIY Province, namely in Putat Village, Gunung Kidul Regency, and Sendangsari Village, Bantul Regency. However, the development activities of SMEs in industrial centers in Indonesia were not optimal, one of the reasons is the management strategy. Therefore, this article contains a comparative study of management styles of development activities, using qualitative research methods, with multiple cases.  The results showed that there was a different management style of SMEs development activities in the wooden batik center, where the management style of the wooden batik center SMEs development activity in Putat Village which was applied by the management of Kopinkra Sumber Rejeki Makmur as a center development institution was authoritarian, so the management system tends to be closed. In contrast to the management style of SMEs development activities in the wooden batik center in Sendangsari Village, which is applied by the Sido Katon Cooperative management as a development center institution assisted by the Pokdarwis Institute and BPDW Krebet Binangun, it is democratic, so the management system tends to be open.